Safety, immunogenicity, and broad-spectrum protective efficacy of a naturally attenuated GCRV-II strain against viral and bacterial challenges in grass carp - Dingzhe Zou; Yifei Li; Jie Zhou; Wangqian Xu; Ying Tian; Run Yang; Yujie Gu; Xiangyu Tian; Yucheng Lin; Jiping Zhang; Weiwei Zeng (Fish & Shellfish Immunology, 2026)

Experimental investigation on adiabatic two-phase frictional pressure drop of R32, R1234ze(E), and their mixtures in a horizontal minichannel - Na Liu; Yeyi Liu; Hao Ji; Dezheng Sun; Run Li; Chuandian Dong; Huan Lin (International Journal of Refrigeration, 2026)

Multifunctional MnO2-based nanozyme scaffold with microenvironment-responsive release for immunomodulation and neuroregeneration in spinal cord injury applications - Ling Peng; Yusong Pan; Jun Tao; Cuilian Wei; Qianqian Liu; Run Huang; Xiuling Lin; Rui Yue (Chemical Engineering Journal, 2026)

Steering active hydrogen in PtCu single atom alloy nanowires for efficient nitrate reduction to ammonia - Weimian Zhang; Binwen Zeng; Haoliang Huang; Fan Dang; Xin Liu; Jing Sun; Wei Liao; Mengxiang Han; Chao Song; Run Ran; Kaiyang Xu; Fei Lin; et al. (Chemical Engineering Journal, 2026)

PFOA promotes PMAIP1–MCL1 apoptotic vulnerability within a BHLHE41-associated macrophage regulatory architecture in atherosclerosis - Hou-liang Chen; Run Wang; Wei-jun Tao; Wang Zhang; Yan-lin Gao; Xiao-bing Cheng (Chemico-Biological Interactions, 2026)

Magnetotelluric strong interference detection and signal reconstruction via recurrence quantification analysis and deep learning - Pei-Lin Zhang; Jia-Qing Wang; Jian-Nan Song; Run-Lin Luo; Ya-Nan Li; Chang-Wei Li (Applied Geophysics, 2026)

Early and prolonged oral edaravone for neuroprotection in acute ischemic stroke: the ERASE-STROKE randomized controlled phase 3 trial - Yang Xiang; Wang-Sheng Jin; Xin-Chen Zhu; Yan Song; Xiao Chen; Qing-Hua Wang; Hao-Lun Sun; Yang Zhao; Xiao-Rong Yu; Tao Feng; Ai-Hong Guo; Hong-Guo Dai; et al. (Science Bulletin, 2026)

Microbial Decomposition of Lignin to Methane Reduces Net Blue Carbon Benefit Across China's Saltmarshes - Leilei Xiao; Chuancheng Fu; Isaac R. Santos; Carlos M. Duarte; Jian Liu; Lifeng Zhou; Meng Zhou; Run Dang; Jinkuo Lin; Kai Xiao; Yongming Luo; Guangxuan Han (Global Change Biology, 2026)
CH 4 emissions from mangrove, saltmarsh, and seagrass ecosystems partially offset carbon sequestration, potentially diminishing the climate mitigation capacity of these blue carbon habitats. However, a mechanistic understanding of the processes governing CH 4 production potential across large spatial scales remains limited. By integrating incubation‐based measurements from 116 sites, we reveal significant ecosystem‐specific differences in CH 4 production potential, with saltmarshes emerging as CH 4 production hotspot relative to mangroves and seagrass meadows. Using an integrated analytical approach encompassing more than 30 environmental, biogeochemical, and microbial parameters, we demonstrate that CH 4 production potential converges on sediment organic carbon availability, particularly plant‐derived carbon, as a key regulatory axis. Additionally, metagenome‐assembled genomes (MAGs) recovered from saltmarshes show a functional bias toward lignin degradation, thereby fueling downstream CH 4 production via methylotrophic pathways. Lignin‐addition and stable carbon isotope experiments further provide supportive evidence that lignin decomposition enhances Chinese saltmarsh CH 4 production potential, revealing a pathway that may reduce net blue carbon benefit. Together, these findings underscore that saltmarsh plant‐derived lignin is less stable than conventionally assumed, as microbial processing redirects stored carbon toward CH 4 production, challenging current blue carbon accounting frameworks at a continental scale within China.

A Musculoskeletal-Finite Element Study of Knee Joint Loading and Cartilage Mechanics in Children with Cerebral Palsy - Dongfei Huo; Run Lin; Junyan Li; Timothy P. Holsgrove; Dominic Farris; Dong Wang; Xijin Hua (Annals of Biomedical Engineering, 2026)
Purpose Cerebral palsy (CP) is typically associated with abnormal gait that may alter knee joint loading and accelerate joint degeneration. We developed an integrated musculoskeletal-finite element (MSK-FE) framework to quantify differences in knee joint biomechanics between children with CP and typically developing (TD) peers. Methods Gait data from 13 children (TD, n = 5; hemiplegia [HP], n = 4; diplegia [DP], n = 4) were analyzed using OpenSim to obtain knee kinematics and compressive knee joint reaction forces (KJRFs). These were applied to scaled 3D FE knee models, incorporating biphasic cartilage, menisci, and ligaments, at the first force peak, mid-stance, and second force peak to evaluate cartilage pressures. Results Compared with TD, both CP subtypes (HP and DP) exhibited greater knee flexion throughout the gait cycle, except for the affected limb in HP (HP A ), which showed reduced flexion during the stance phase. Peak KJRFs over the gait cycle were slightly higher in DP and HP A than in TD, whereas the unaffected limb in HP (HP UA ) generated the highest peak KJRFs among all groups, indicating compensatory overloading of the unaffected limb in HP. Correspondingly, FE analysis showed that peak cartilage contact pressures in the HP cohorts were significantly higher than in DP and TD, while pressures in DP were slightly higher than in TD over the gait cycle. The HP UA showed the highest contact pressures among all groups. Conclusion The MSK-FE framework quantified knee loading and cartilage contact pressure patterns in children with CP. These preliminary findings highlight subtype- and limb-specific gait-loading patterns and provide a mechanistic basis for future larger-scale and longitudinal investigations.

A comprehensive review on the chemical composition, pharmacological effects and quality evaluation of Gentiana straminea Maxim. - Yuan-Wen Zhuang; Min Wang; Jian-Tao Zhao; Yu-Qing Wang; Run-Qian Yu; Huan Xia; Xiao-Hong Wei; Peng-Cheng Lin; Gui-Yang Xia; Sheng Lin (Journal of Natural Medicines, 2026)

Boosting char formation in lignin aerogels via PN synergy: A route to flame retardancy and multifunctional performance - Jia-Hui Wang; Tao Gui; Shuang-Lin Zou; Qing-Hua Wang; Ying-Chun Xu; Rong Tan; Qiang Wang; Ling-Ping Xiao; Run-Cang Sun (Chemical Engineering Journal, 2026)

Galacto-oligosaccharides enrich galactosidase-encoded rather than all Lachnospiraceae bacteria to redress abnormal gut microbiota and lipid metabolism in pregnancy - Rujun Wei; Jiyun Long; Haoxue Xia; Yanni Sun; Lin Zhang; Xiaoqing Li; Hongping Zhang; Run Wang; Shengtao Gao; Yunwei Chen; Yun Gu; Xiaoya Wang; et al. (Science China Life Sciences, 2026)

Nondecomposer-mediated nutrient transfer in soils: experimental evidence from Drosophila - Yunchao Luo; Run Liu; Tingting Cao; Jiayue Zhang; Mengna Zhao; Ke Li; Zunian Ran; Lin Wang; Xingjun Tian (Applied Soil Ecology, 2026)

Identification and functional characterization of Z-DNA in plants - Yonghang Run; Xinyan Chen; Lin Dai; Zhiyun Gong; Wenli Zhang (Trends in Plant Science, 2026)

Pharmacotranscriptomics-based discovery and hydrogel-mediated delivery of drug combinations for potentiated cancer immunotherapy - Rong Liu; Hui-Han Yu; Wei-Rong Li; Jia-Si Wu; Jing-Yang Zhang; Jia-Qi Luo; Yu Pang; Ying Chen; Yan-Dan Yao; Run Lin; Ling Wang; Jin-Zhi Du; et al. (Science Bulletin, 2026)

Can karst aquifer for public supply threatened by lead smelting be sustainably managed? Part I: Evidence from lead isotopes - Bei-Yi Xu; Run-Zhi Xie; Song-Lin Liu; Jian-Ming Zhu; Wu-Tian Cai; Yan Zheng (Geochimica et Cosmochimica Acta, 2026)

Corrosion behavior and biocompatibility of MgZnP@PDA coatings on biodegradable Zn2Cu alloy - Rui Yue; Suqin Wang; Yusong Pan; Yusheng Zuo; Xiancai Meng; Gaozhi Jia; Xiuling Lin; Run Huang; Shaoding Sheng; Lingyu Li (Chemical Engineering Journal, 2026)

Whole-genome sequencing reveals the genetic diversity of Aeromonas from freshwater fish and the presence of novel genomic islands carrying clinically important antimicrobial resistance genes - Xiao-Qin Wang; Ke Wu; Run-Min Kang; Heng Lin; Lu-Ya Liu; Ting Xian; Yi-Zhi Tang; Xin Yang; An-Yun Zhang; Hong-Ning Wang; Chang-Wei Lei (Aquaculture, 2026)

Prediction on uplift displacement of tunnel induced by base grouting in soft clay - Jia-run Wu; Yu-liang Lin; Dan He; Ye Ma (Tunnelling and Underground Space Technology, 2026)

Short-, medium-, and long-chain chlorinated paraffins in sediments from the Pearl River Delta, China: Occurrence, sources, and risks - Fei-Xiang Xie; Yu-Fang Huang; Yong-Hong Zhang; Ya-Hui Xue; Run-Lin Chen; Xiao-Mei Huang; Hong-De Shi; Jia-Hui Huang; Hui-Ru Li (Science of The Total Environment, 2026)

Mercury isotope perspectives on vegetation-enhanced nickel mobilization and migration during laterite formation - Ruo-Lin Liu; Martin Yan Hei Li; Run-Sheng Yin; Mei-Fu Zhou; Jun-Hong Zhao (Geochimica et Cosmochimica Acta, 2026)

Advanced functionalization strategies of chitin and chitosan toward sustainable nanocomposites - Shuang-Lin Zou; Xin-Ran Liu; Jia-Hui Zhang; Ying-Chun Xu; Qiang Wang; Ling-Ping Xiao; Run-Cang Sun (Carbohydrate Polymers, 2026)

Genome-wide analysis of the sugarcane SUT gene family reveals ShSUT4 as a key regulator of abiotic stress responses - Xue-Ting Zhao; Ahmad Ali; Cui-Lian Feng; Ji-Shan Lin; Rui-Jie Wu; Shu-Zhen Zhang; Guang-Run Yu; Hai-Feng Jia; Yu-Qing Gong; Ting-Ting Zhao; Jun-Gang Wang (Theoretical and Applied Genetics, 2026)

Oral Administrations of Short-Chain Fatty Acids or Probiotics Extend the Survival Times and Mitigate the Neuropathological Damages in the Scrapie-Infected Hamsters - Yuan Wang; Dong-Lin Liang; Run-Dong Cao; Ruhan A.; Jia-Feng Zeng; Bing Xu; Ju-Zheng Li; Wei-Wei Zhang; Li-Ping Gao; Kang Xiao; Xiao-Ping Dong; Qi Shi (Molecular Neurobiology, 2026)

Cassane diterpenoids with hepatic gluconeogenesis inhibitory activity from the seeds of Caesalpinia decapetala (Roth) Alston - De-Sheng Wang; Yu Shen; Lin-Fen Ding; Run-Cheng Yan; Ming Hu; Wen-Chao Tu; Liu-Dong Song; Suling Huang; Xing-De Wu (Phytochemistry, 2025)

Fast Forward Modeling of Resistivity Method under Complex Topography Using Finite Element Method - Zhan Wang; Chang-Wei Li; Yu-Zeng Lv; Run-Lin Luo; Bo Cheng; Bo Li (Applied Geophysics, 2025)

System temperature prediction and verification of all-sky electrostatic analyzer on the lunar surface - Tsung-Pin Hung; Chih-Yu Chiang; Tzu-Fang Chang; Zhao-Yu Huang; Yu-Rong Cheng; Sheng-Cheng Tsai; Tzu-En Yen; Jih-Run Tsai; Shin-Fa Lin (Advances in Space Research, 2025)

Laminaria Japonica hydrolysate as a novel biostimulant for enhancing DHA accumulation in Aurantiochytrium limacinum - Jia-Xue Lin; Ying Wang; Shao-Geng Zhao; Bei-Chen Huang; Yue Zhang; Zhi-Qiang Wang; Sheng-Jie Li; Qian Liu; Yan Ma; Jing-Run Ye; Hai-Ying Wang; Zhi-Peng Wang (World Journal of Microbiology and Biotechnology, 2025)

Target analysis of per- and polyfluoroalkyl substances in surface water: Occurrence, seasonal trends, and risk-based prioritization in the Minjiang River - Hui Zhang; Xin-Yue Wang; Yu-Hua Zheng; Jing-Run Hu; Xiao-Lin Li; Hong-Ling Yin; Rui Xiao; Xiao-Lan Zhu; Ting Chen; Huan Chen (Science of The Total Environment, 2025)

Vortex-Induced Vibration Analysis of FRP Composite Risers Using Multivariate Nonlinear Regression - Lin Zhang; Chunguang Wang; Wentao He; Keshun Ma; Run Zheng; Chiemela Victor Amaechi; Zhenyang Zhang (Journal of Marine Science and Engineering, 2025)
Marine risers are essential for offshore resource extraction, yet traditional metal risers encounter limitations in deep-sea applications due to their substantial weight. Fiber-reinforced polymer (FRP) composites offer a promising alternative with advantages including low density and enhanced corrosion/fatigue resistance. However, FRP risers remain susceptible to fatigue damage from vortex-induced vibration (VIV). Therefore, this study investigated VIV behavior of FRP composite risers considering the coupled effect of tensile-flexural moduli, top tensions, slenderness ratios, and flow velocities. Through an orthogonal experimental design, eighteen cases were analyzed using multivariate nonlinear fitting. Results indicated that FRP composite risers exhibited larger vibration amplitudes than metal counterparts, with amplitudes increasing to both riser length and flow velocity. It was also found that the optimized FRP configuration demonstrated enhanced fiber strength utilization. Parameter coupling analysis revealed that the multivariate nonlinear fitting model achieved sufficient accuracy when incorporating two coupled parameters, with the most significant interaction occurring between flexural modulus and top tension.

Identification and comparative analysis of flowering genes in the Sugar pathway from five Gossypium species - Lei-Ming Liu; Chuan-Bo Jiang; Yi-Lin Yang; Tian-Run Mei; Ruo-Fei Liu; Hai-Liang Liu; Xian-Zhong Huang (Plant Gene, 2025)

Arbuscular mycorrhizal fungi enhance Leymus chinensis resistance to salinity predominantly through regulating root endosphere bacteria - Peiran Guo; Yazhou Hou; Bingbing Jia; Yuchen Wang; Chengyan Lu; Run Wang; Jiaying Lin; Yanan Zhang; Wei Guo; Frank Yonghong Li (Plant and Soil, 2025)

Emission characteristics, environmental impact, and occupational health risks assessment of volatile organic compounds (VOCs) in the hairdressing sector - Run Hao; Xinmiao Lin; Zhen Yao; Meng Wang; Jianling Sun; Hailin Wang (Atmospheric Pollution Research, 2025)

The link between eye movements and cognitive function in mild to moderate Alzheimer’s disease - Xiao-ting Ma; Lin-lin Yao; Shan-wen Liu; Xiao-fen Weng; Run-ying Bao; Yi-fan Yang; Yi-feng Li; Yan-yun Sun; Dan Xu; Zhen-yu Jia; Hua Hu (Experimental Brain Research, 2025)

Clock bias prediction of navigation satellite based on BWO-CNN-BiGRU-attention model - Wenlong Sun; Jinping Chen; Caibo Hu; Yongxin Lin; Maolei Wang; He Zhao; Run Zhao; Guitao Fu; Tan Zhao (GPS Solutions, 2025)

Sustainable utilization of phosphorus-rich sludge in cement composites: Multiscale evaluation and mechanistic analysis - Shengli Ren; Zhirong Xu; Benqin Yang; Xiao-Yong Wang; Yi Han; Run-Sheng Lin; Yongpang Liao (Journal of Environmental Chemical Engineering, 2024)

Assessment of multidimensional diversity and conservation of threatened timber trees in China under climate change - Jian-Lin Hu; Xiu-Qin Ci; Xiao-Yan Zhang; Run Zhou; Jian-Hua Xiao; Zhi-Fang Liu; Can-Yu Zhang; Xuan Jin; Jie Li (Biological Conservation, 2024)

Structurally diverse diterpenoids from the seeds of Caesalpinia minax Hance and their bioactivities - Wen-Chao Tu; Lin-Fen Ding; Liu-Dong Song; Yong-Jiao Li; Run-Cheng Yan; Yun Wu; Wei-Yang Feng; Xing-De Wu (Phytochemistry, 2024)

Vibration reduction and efficiency enhancement effects of twisted rudders in submarines under small rudder angle conditions - Di Zhang; Jin-ming Ye; Wan-li Yang; Yuan-run Wu; Jian-lin Shou (Ocean Engineering, 2024)

Corrigendum to “Ionic-confining-assisted multiple-mode tunable light emitting of carbon nanodots” [Chem. Eng. J. 486 (2024) 150196] - Jing-Nan Hao; Zhong-Zheng Ding; Cheng-Long Shen; Guang-Song Zheng; Jia-Lu Liu; Ruo-Bing Li; Run-Wei Song; Kai-Kai Liu; Jin-Hao Zang; Lin Dong; Qing Lou; Chong-Xin Shan (Chemical Engineering Journal, 2024)

Tough and biodegradable C-lignin cross-linked polyvinyl alcohol supramolecular composite films with closed-looping recyclability - Tao Gui; Ling-Ping Xiao; Shuang-Lin Zou; Yue Zhang; Xu Fu; Chang-Hao Liu; Run-Cang Sun (Chemical Engineering Journal, 2024)

Characterization of a pangolin SARS-CoV-2-related virus isolate that uses the human ACE2 receptor - Luo-Yuan Xia; Xue-Feng Wang; Xiao-Ming Cui; Yi-Ming Zhang; Zhen-Fei Wang; En-Tao Li; Chang-Fa Fan; Ke Song; Yuan-Guo Li; Run-Ze Ye; Fang-Xu Li; Dai-Yun Zhu; et al. (Science China Life Sciences, 2024)

Structure and dynamics of microbial communities associated with the resurrection plant Boea hygrometrica in response to drought stress - Run-Ze Sun; Yuan-Yuan Wang; Xiao-Qiang Liu; Zhao-Lin Yang; Xin Deng (Planta, 2024)

Anti-pancreatic cancer activity of cassane diterpenoids isolated from the seeds of Caesalpinia sappan mediated by autophagy activation via ROS/AMPK/mTORC1 pathway - Jia Su; De-Sheng Wang; Guo-Xian Hu; Yu-Yao Liu; Ming Hu; Ya Chen; Qi-Qi Wang; Run-Cheng Yan; Yun Wu; Yong-Jiao Li; Ke Ma; Yan-Yan Qi; et al. (Phytochemistry, 2024)

Seasonal predictability of SST anomalies and marine heatwaves over the Kuroshio extension region in the Copernicus C3S models - Chenguang Zhou; Hong-Li Ren; Yu Geng; Run Wang; Lin Wang (Ocean Modelling, 2024)

Produce low-CO2 silica fume hybrid high-strength concrete using dry ice (solid CO2) as a CO2-utilized admixture - Mei-Yu Xuan; Run-Sheng Lin; Yi Han; Gui-yu Zhang; Cheng Guo; Xiao-Yong Wang (Journal of Cleaner Production, 2024)

Synergistically Augmenting Cancer Immunotherapy by Physical Manipulation of Pyroptosis Induction - Chenyang Zhao; Tingting Zheng; Run Wang; Xiaona Lin; Zhengming Hu; Zhuofei Zhao; Zhifei Dai; Desheng Sun (Phenomics, 2024)
Pyroptosis is a newly recognized type of programmed cell death mediated by the gasdermin family and caspase. It is characterized by the formation of inflammasomes and the following inflammatory responses. Recent studies have elucidated the value of pyroptosis induction in cancer treatment. The inflammatory cytokines produced during pyroptosis can trigger immune responses to suppress malignancy. Physical approaches for cancer treatment, including radiotherapy, light-based techniques (photodynamic and photothermal therapy), ultrasound-based techniques (sonodynamic therapy and focused ultrasound), and electricity-based techniques (irreversible electroporation and radiofrequency ablation), are effective in clinical application. Recent studies have reported that pyroptosis is involved in the treatment process of physical approaches. Manipulating pyroptosis using physical approaches can be utilized in combating cancer, according to recent studies. Pyroptosis-triggered immunotherapy can be combined with the original anti-tumor methods to achieve a synergistic therapy and improve the therapeutic effect. Studies have also revealed that enhancing pyroptosis may increase the sensitivity of cancer cells to some physical approaches. Herein, we present a comprehensive review of the literature focusing on the associations between pyroptosis and various physical approaches for cancer and its underlying mechanisms. We also discussed the role of pyroptosis-triggered immunotherapy in the treatment process of physical manipulation.

Offshore Renewable Energy - Jijian Lian; Qiang Fu; Lin Cui; Run Liu; Bingyong Guo (Journal of Marine Science and Engineering, 2024)
Offshore renewable energy is an abundant clean energy source that includes offshore solar energy, offshore wind power, wave energy, ocean thermal energy conversion (OTEC), and tidal energy [...]

Preparing a heavy-metal adsorbent based on alginate-like extracellular polymers from conventional activated sludge via polyethyleneimine grafting - Chen Shi; Run-Gen Zeng; Shi-Chao Yuan; Lin Zhang; Xiang-Yang Wang; Li-Ting Hao; Xiao-Di Hao; Nan Zhang; Yuan-Yuan Wu (Sustainable Chemistry and Pharmacy, 2024)

The association between artificial light at night and gestational diabetes mellitus: A prospective cohort study from China - Junhao Liao; Chuan Yu; Jiarui Cai; Run Tian; Xingyue Li; Hong Wang; Lin Li; Guishuang Song; Leyao Fu; Xinxi Li; Qiaoyue Ge; Ling Zhang; et al. (Science of The Total Environment, 2024)

Ionic-confining-assisted multiple-mode tunable light emitting of carbon nanodots - Jing-Nan Hao; Zhong-Zheng Ding; Cheng-Long Shen; Guang-Song Zheng; Jia-Lu Liu; Ruo-Bing Li; Run-Wei Song; Kai-Kai Liu; Jin-Hao Zang; Lin Dong; Qing Lou; Chong-Xin Shan (Chemical Engineering Journal, 2024)

Soil aggregate-associated organic carbon mineralization and its driving factors in rhizosphere soil - Jun-Ya Li; Peng Chen; Zhi-Guo Li; Lin-Yang Li; Run-Qin Zhang; Wei Hu; Yi Liu (Soil Biology and Biochemistry, 2023)

The way to elastic ferroelectrics - Ben-Lin Hu; Brahim Dkhil; Run-Wei Li (Science Bulletin, 2023)

Integrated MOVES model and machine learning method for prediction of CO2 and NO from light-duty gasoline vehicle - Run Liu; Hong-di He; Zhe Zhang; Cui-lin Wu; Jin-ming Yang; Xing-hang Zhu; Zhong-ren Peng (Journal of Cleaner Production, 2023)

Characterization of a gE/gI/TK gene-deleted pseudorabies virus variant expressing the Cap protein of porcine circovirus type 2d - Rui-Qin Xu; Lin-Qing Wang; Hui-Hua Zheng; Run-Bo Tian; Lan-Lan Zheng; Shi-Jie Ma; Hong-Ying Chen (Comparative Immunology, Microbiology and Infectious Diseases, 2023)

Construction ceramsite from low-silicon red mud: Design, preparation, and sintering mechanism analysis - Zhuo Liu; Rongxin Guo; Xiao-Yong Wang; Chaoshu Fu; Run-sheng Lin (Process Safety and Environmental Protection, 2023)

Characteristics of spatial and temporal carbon emissions from different land uses in Shanxi section of the Yellow River, China - Lin Zhao; Meng-na Chen; Chuan-hao Yang; Run-ze Zhang; Qi-peng Zhang; Qian Wang (Environment, Development and Sustainability, 2023)

Overexpression of OsNF-YB4 leads to flowering early, improving photosynthesis and better grain yield in hybrid rice - Meifang Peng; Feng Gan; Xiaomin Lin; Run Yang; Shaoyi Li; Wei Li; Lan Wu; Xiaoli Fan; Kegui Chen (Plant Science, 2023)

Association between nitrogen dioxide concentration and hypertension hospitalization: A multicenter time-series analysis in Xinxiang, China - Shi-qi Ge; Yong-bin Wang; Fei Lin; Run-ran Miao; Kai Zhang; Li Li; Hui-ge Guo; Qian Wang; Li Zhang; Zhi-gang Chen; Guo-an Zhao (Atmospheric Pollution Research, 2023)

Trehalose prevents glyphosate-induced hepatic steatosis in roosters by activating the Nrf2 pathway and inhibiting NLRP3 inflammasome activation - Cai-Yu Lian; Run-Zhou Wang; Jie Wang; Zhen-Yong Wang; Wei Zhang; Lin Wang (Veterinary Research Communications, 2023)

Failure mechanism of a large-scale composite deposits caused by the water level increases - Xin Zhang; Guo-xiang Tu; Qi-feng Luo; Hao Tang; Yu-lin Zhang; An-run Li (Journal of Mountain Science, 2023)

Valorization of lignin through reductive catalytic fractionation of fermented corn stover residues - Wen-Zheng Yin; Ling-Ping Xiao; Shuang-Lin Zou; Wen-Xin Li; Hongliang Wang; Run-Cang Sun (Bioresource Technology, 2023)

Highly selective monoclonal antibody-based fluorescence immunochromatographic assay for the detection of fenpropathrin in vegetable and fruit samples - Zi-Hong Xu; Jun-Kai Wang; Qiu-Xiong Ye; Lin-Feng Jiang; Hao Deng; Jun-Fa Liang; Run-Xi Chen; Wei Huang; Hong-Tao Lei; Zhen-Lin Xu; Lin Luo (Analytica Chimica Acta, 2023)

Biotransformation of sulfamonomethoxine in a granular sludge system: Pathways and mechanisms - Meng-Yuan Li; Run-Dong Zhang; Yi-Xing Lin; Qi-Wen Li; Qiu-Yue Zhao; Zong-Xi Zhao; Zhong-Ming Ling; Long-Fei Shu; Min Zhang; Li-Xin Hu; Yi-Jing Shi; Guang-Guo Ying (Chemosphere, 2023)

Seasonal spermatogenesis, epididymal storage, and creatine kinase expression in Pelodiscus sinensis - Yu-Fei Yang; Jia-Hao Wu; Run-Lan Lin; Shang-Jun Yin; Guo-Ying Qian; Wei Wang; Yong-Doo Park (Animal Reproduction Science, 2023)

Euphanoids A and B, two new lathyrane diterpenoids with nitric oxide (NO) inhibitory activity from Euphorbia kansuensis - Xue-Long Yan; Run-Zhu Fan; Jun Sang; Xing-Lin Xie; Gui-Hua Tang; Sheng Yin (Natural Product Research, 2021)

Comparative performance assessment of landslide susceptibility models with presence-only, presence-absence, and pseudo-absence data - Dong-mei Zhao; Yuan-mei Jiao; Jin-liang Wang; Yin-ping Ding; Zhi-lin Liu; Cheng-jing Liu; Ying-mei Qiu; Juan Zhang; Qiu-e Xu; Chang-run Wu (Journal of Mountain Science, 2020)

A role of age-dependent DNA methylation reprogramming in regulating the regeneration capacity of Boea hygrometrica leaves - Run-Ze Sun; En-Hui Zuo; Jin-Feng Qi; Yang Liu; Chih-Ta Lin; Xin Deng (Functional & Integrative Genomics, 2020)

Insights into transcriptional characteristics and homoeolog expression bias of embryo and de-embryonated kernels in developing grain through RNA-Seq and Iso-Seq - Jun Wei; Hong Cao; Jing-dong Liu; Jing-hong Zuo; Yu Fang; Chih-Ta Lin; Run-ze Sun; Wen-long Li; Yong-xiu Liu (Functional & Integrative Genomics, 2019)

Kitamycin C, a new antimycin-type antibiotic from Streptomyces antibioticus strain 200-09 - Fan Wang; Shu-Na Fu; Yi-Xuan Bao; Yu Yang; Hui-Fang Shen; Bi-Run Lin; Guang-Xiong Zhou (Natural Product Research, 2017)

The In vitro/vivo Evaluation of Prepared Gastric Floating Tablets of Berberine Hydrochloride - Jun Ji; Xin He; Xiao-Lin Yang; Wen-Juan Du; Cheng-Long Cui; Ling Wang; Xue Wang; Chun-Feng Zhang; Chang-Run Guo (AAPS PharmSciTech, 2017)

Physical‐biological coupling of N 2 fixation in the northwestern S outh C hina S ea coastal upwelling during summer - Run Zhang; Min Chen; Qing Yang; Yuanshao Lin; Huabin Mao; Yusheng Qiu; Jinlu Tong; E. Lv; Zhi Yang; Weifeng Yang; Jianping Cao (Limnology and Oceanography, 2015)
Here, we present the first combined results of N 2 fixation rates ( 15 N 2 assay), dissolved iron (dFe, 14 C assay) in the northwestern South China Sea (NWSCS) coastal upwelling region during summer. Surface N 2 fixation rate ranged between 0.1 nmol N L −1 d −1 and 5.6 nmol N L −1 d −1 (average 1.0 nmol N L −1 d −1 , n = 50) under nonbloom conditions. At a Trichodesmium bloom station, N 2 fixation rate was ∼ 3 orders of magnitude higher. Depth‐integrated N 2 fixation rate ranged between 7.5 μmol N m −2 d −1 and 163.1 μmol N m −2 d −1 (average 46.4 μmol N m −2 d −1 ). Our results indicate that N 2 fixation is unlikely limited by Fe availability in the NWSCS continental waters, instead, the coastal upwelling‐induced combined effects of physical and biological processes may have played a decisive role. With the upwelled cold, dFe‐rich, nutrient‐replete waters, nondiazotrophic phytoplankton growth would be preferentially enhanced while N 2 fixation was hindered due to relative deficiency of phosphate caused by massive phytoplankton utilization in the coastal upwelling. By comparison, N 2 fixation was notably elevated along with decreased PP in the offshore waters, probably due to a shift from P‐deficiency to N‐deficiency. Consistently, the contribution of N 2 fixation to PP (0.01–2.52%) also increased toward the open waters. As a significant external N source, summertime N 2 fixation is estimated to contribute a flux of 1.4 Gmol N to this area under nonbloom conditions. This study adds to the knowledge of N 2 fixation in the rarely studied subtropical coastal upwellings, and highlights the necessity of future comprehensive studies in such highly dynamic environments.

3D density inversion of gravity gradient data using the extrapolated Tikhonov regularization - Jin-Zhao Liu; Lin-Tao Liu; Xing-Hui Liang; Zhou-Run Ye (Applied Geophysics, 2015)

Effect of the CYP2C19*2 and *3 genotypes, ABCB1 C3435T and PON1 Q192R alleles on the pharmacodynamics and adverse clinical events of clopidogrel in Chinese people after percutaneous coronary intervention - Xiao-Fang Tang; Jing Wang; Jia-Hui Zhang; Xian-Min Meng; Bo Xu; Shu-Bin Qiao; Yong-Jian Wu; Jue Chen; Yuan Wu; Ji-Lin Chen; Run-Lin Gao; Jin-Qing Yuan; et al. (European Journal of Clinical Pharmacology, 2013)

Effect of Zinc Source on Performance, Zinc Status, Immune Response, and Rumen Fermentation of Lactating Cows - Run L. Wang; Jian G. Liang; Lin Lu; Li Y. Zhang; Su F. Li; Xu G. Luo (Biological Trace Element Research, 2013)

Selective pressure dominates the synonymous codon usage in parvoviridae - Sheng-Lin Shi; Yi-Ren Jiang; Yan-Qun Liu; Run-Xi Xia; Li Qin (Virus Genes, 2013)

Identification of a new gene encoding 5-enolpyruvylshikimate-3-phosphate synthase using genomic library construction strategy - Chang-Yan Zhou; Yong-Sheng Tian; Zhi-Sheng Xu; Wei Zhao; Chen Chen; Wen-Hua Bao; Lin Bian; Run Cai; Ai-Zhong Wu (Molecular Biology Reports, 2012)

XRCC1 Arg399Gln and clinical outcome of platinum-based treatment for advanced non-small cell lung cancer: a meta-analysis in 17 studies - Jian Chen; Qing-wei Zhao; Gen-ming Shi; Lin-run Wang (Journal of Zhejiang University-SCIENCE B, 2012)

Construction of self-cloning, indigenous wine strains of Saccharomyces cerevisiae with enhanced glycerol and glutathione production - Rui-Ying Hao; Yan-Lin Liu; Zhao-Yue Wang; Bo-run Zhang (Biotechnology Letters, 2012)

Expression patterns of prion protein gene in differential genotypes sheep: quantification using molecular beacon real-time RT-PCR - Chuan Wang; Run Wu; Fa-Di Li; Lei Liu; Xiao-Li Zhang; Chun-Lin Zhao; Xiao-Long Diao; Hong-Wei Guan (Virus Genes, 2011)

RRM1 gene expression in peripheral blood is predictive of shorter survival in Chinese patients with advanced non-small-cell lung cancer treated by gemcitabine and platinum - Lin-run Wang; Guo-bing Zhang; Jian Chen; Jun Li; Ming-wei Li; Nong Xu; Yang Wang; Jian-zhong Shen Tu (Journal of Zhejiang University-SCIENCE B, 2011)

Effect of Dietary Supplementation with Copper Sulfate or Tribasic Copper Chloride on the Growth Performance, Liver Copper Concentrations of Broilers Fed in Floor Pens, and Stabilities of Vitamin E and Phytase in Feeds - Lin Lu; Run L. Wang; Zheng J. Zhang; Fred A. Steward; Xugang Luo; Bin Liu (Biological Trace Element Research, 2010)

Comparison of pharmacokinetics, efficacy and toxicity profile of gemcitabine using two different administration regimens in Chinese patients with non-small-cell lung cancer - Lin-run Wang; Jian Liu; Ming-zhu Huang; Nong Xu (Journal of Zhejiang University-SCIENCE B, 2007)

Pharmacokinetics of gemcitabine in Chinese patients with non-small-cell lung cancer - Lin-run Wang; Ming-zhu Huang; Nong Xu; Jian-zhong Shentu; Jian Liu; Jie Cai (Journal of Zhejiang University-SCIENCE B, 2005)

Arbuscular mycorrhizal status of wild plants in saline-alkaline soils of the Yellow River Delta - Jian-Min Zhou; Xian-Gui Lin; Fa-Yuan Wang; Run-Jin Liu (Mycorrhiza, 2004)